2011
DOI: 10.1071/bt10267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different methods for assessing the reproductive mode of weeping lovegrass plants, Eragrostis curvula (Schrad.) Nees

Abstract: Weeping lovegrass is a forage grass cultivated in semiarid regions of the world that reproduces mainly by apomixis (diplospory), a process that involves the formation of asexual seeds and bypasses the processes of meiosis and fertilisation. The aim of this work was to evaluate and compare different techniques (cytoembryology, callose deposition, flow cytometry and progeny tests) to determine the reproductive mode of weeping lovegrass. Typical sexual and apomictic processes were clearly differentiated using cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…The observed of embryo sacs correspond to a Polygonum type, which has a typical structure of Paniceae (Anton & Cocucci, ), similar to the sexual sacs of Panicum elephantipes Nees (Urbani, ). Constitutions of these mature embryo sacs are almost indistinguishable from diplosporic unreduced ones by structural observation (Meier et al., ), but the wide extent of hybrids among progeny, as we found with the hybrid origin test on the four crosses in A. macrum , is attributable to a sexual origin of all of the 33 members of their progeny. Although a small fraction of the putative hybrids could not be demonstrated to have derived from the cross, the presence of a unique band, absent in both the mother and the putative father, is strong evidence that these putative nonhybrids did not result from an apomictic origin.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The observed of embryo sacs correspond to a Polygonum type, which has a typical structure of Paniceae (Anton & Cocucci, ), similar to the sexual sacs of Panicum elephantipes Nees (Urbani, ). Constitutions of these mature embryo sacs are almost indistinguishable from diplosporic unreduced ones by structural observation (Meier et al., ), but the wide extent of hybrids among progeny, as we found with the hybrid origin test on the four crosses in A. macrum , is attributable to a sexual origin of all of the 33 members of their progeny. Although a small fraction of the putative hybrids could not be demonstrated to have derived from the cross, the presence of a unique band, absent in both the mother and the putative father, is strong evidence that these putative nonhybrids did not result from an apomictic origin.…”
Section: Discussionsupporting
confidence: 68%
“…Diversity analysis by phenotypic or genotypic traits is one of the current support tools to study the reproduction mode of populations and through a proper design of cross progeny test. Molecular genetic markers are the most reliable for the study of segregation among progeny to infer the mode of reproduction (Acuña et al, 2005;Daurelio, Espinoza, Quarin, & Pessino, 2004;Schranz el al., 2006;Meier et al, 2011;Barrett, 2013;Garcia, Vigna, Sousa, Jungmann, & Cidade, 2013;Kozub et al, 2017). Adequate markers would be unlinked and monogenically inherited.…”
Section: Crop Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that in 2009 the plant continued to display a level of apomixis as high as that in 200713. Therefore, the rate of apomixis in colchiploid plant C shifted from near 0% in 2003 (21) to 85–90% in 2007 (16), and remained at similar values in 2009 (89,7%).…”
Section: Resultsmentioning
confidence: 87%
“…The most useful cultivars for forage are tetraploids (2n = 4x = 40) that reproduce by pseudogamous diplosporous apomixis (Crane 2001, Voigt et al 2004. In this asexual reproduction through seeds (Asker and Jerling 1992), the megasporocyte undergoes two rounds of mitotic division to form a non-reduced tetranucleate embryo sac with an egg, two synergids, and one polar nucleus (Meier et al 2011). Besides Eragrostis, diplosporous apomixis has been described in Agropyrum, Boechera, Paspalum, Poa, Tripsacum among other species (Nogler 1984, Barcaccia andAlbertini 2013).…”
Section: Introductionmentioning
confidence: 99%